“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Two-dimensional electron bound hole photoluminescence in GaAs in perpendicular magnetic fields - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

High-precision determination of silicon nanocrystals: optical spectroscopy versus electron microscopy - Köthemann, Ronja; Weber, Nils; Lindner, Jörg K N; Meier, Cedrik (Semiconductor Science and Technology)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Structural, electronic and phononic properties of PtSe2: from monolayer to bulk - Kandemir, A; Akbali, B; Kahraman, Z; Badalov, S V; Ozcan, M; Iyikanat, F; Sahin, H (Semiconductor Science and Technology)

Interlayer charge transfer in n-modulation doped Al1−x Ga x As–GaAs single heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Influence of recombination center interaction on the photoluminescence of AlGaAs/GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

On the annealing mechanism of AuGe/Ni/Au ohmic contacts to a two-dimensional electron gas in GaAs/AlxGa1−xAs heterostructures - Koop, E J; Iqbal, M J; Limbach, F; Boute, M; van Wees, B J; Reuter, Dirk; Wieck, A D; Kooi, B J; van der Wal, C H (Semiconductor Science and Technology)

In situ characterization of ZnTe epilayer irradiation via time-resolved and power-density-dependent Raman spectroscopy - Wiedemeier, V; Berth, Gerhard; Zrenner, Artur; Larramendi, E M; Woggon, U; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Laser irradiation damage in ZnTe epilayers was analyzed in situ by power-density-dependent and time-resolved micro-Raman spectroscopy. Damage by ablation or compound decomposition on the sample surface was revealed by the decrease of the ZnTe–nLO mode intensity with the increase of laser power density. The appearance of the peaks associated with the stronger crystalline-tellurium modes, tellurium aggregates and second-order Raman scattering at room temperature μ-Raman spectra was observed for higher power densities than 4.4 × 105 W cm−2. The Raman signal time transients of ZnTe–nLO and crystalline-tellurium modes reveal an exponential evolution of the laser irradiation damage and a fast formation of crystalline tellurium aggregates on the layer surface.

Application of the discontinous Galerkin time domain method to the optics of metallic nanostructures - Grynko, Yevgen; Förstner, Jens; Meier, Torsten (AAPP | Atti della Accademia Peloritana dei Pericolanti)
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. The model is used to compute the linear and nonlinear optical response of split ring resonators and to study physical mechanisms that contribute to second harmonic generation.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Intensity enhancement of Te Raman modes by laser damage in ZnTe epilayers - Larramendi, E M; Berth, Gerhard; Wiedemeier, V; Hüsch, K-P; Zrenner, Artur; Woggon, U; Tschumak, E; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Damage caused by laser irradiation on the surface of ZnTe epilayers was studied by micro-Raman and atomic force microscopy (AFM). ZnTe LO-phonon overtones up to four order and TO + (n − 1)LO zone-center phonons were observed in the resonant micro-Raman spectra at room temperature. Discrepancies in the literature regarding the origin of two features observed at low frequencies around 120 and 140 cm−1 in the Raman spectrum of ZnTe are discussed and resolved. These Raman peaks were not detected by using a low excitation laser power density on a Zn-terminated ZnTe surface; however, with the increase of the laser power density they were found to arise irreversibly. The correspondence of these peaks in a wave number with the strongest Raman peaks of the crystalline tellurium phase and the intensity enhancement behavior with the laser power in a similar way as for CdTe strongly suggests the formation of crystalline tellurium aggregates on the layer surface due to laser irradiation damage. AFM data reveal the occurrence of laser ablation on the ZnTe surface even though the surface temperature of the sample is below the melting point.

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Preparation of electron waveguide devices on GaAs/AlGaAs using negative-tone resist calixarene - Knop, M; Richter, M; Maßmann, R; Wieser, U; Kunze, U; Reuter, Dirk; Riedesel, C; Wieck, A D (Semiconductor Science and Technology)

Dual-gate GaAs/AlGaAs quantum point contact with tuneable subband energy separation - Kähler, D; Knop, M; Kunze, U; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Influence of processing parameters on the transport properties of quantum point contacts fabricated with an atomic force microscope - Apetrii, G; Fischer, S F; Kunze, U; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Local two-dimensional electron gas formation in p-doped GaAs/InyGa1 yAs/AlxGa1 xAs heterostructures by focused Si-implantation doping - Reuter, D; Meier, Cedrik; Riedesel, C; Wieck, A D (Semiconductor Science and Technology)

Layer-compensated selectively doped AlxGa1-xAs/GaAs heterostructures as a base material for nanolithography - Reuter, Dirk; Kähler, D; Kunze, U; Wieck, A D (Semiconductor Science and Technology)

Layer-compensated selectively doped AlxGa1-xAs/GaAs heterostructures as a base material for nanolithography - Reuter, Dirk; Kähler, D; Kunze, U; Wieck, A D (Semiconductor Science and Technology)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)

Coherent Dynamics of Exciton Wavepackets in Semiconductor Heterostructures - Meier, Torsten; Koch, M.; Feldmann, J.; Göbel, E.O.; Jahnke, F.; Schäfer, W.; Thomas, P.; Koch, S.W.; Nickel, H.; Luttgen, S.; Stolz, W. (Proceedings der 8. International Winterschool on New Developments in Physics)
The coherent dynamics of exciton wavepackets in (GaIn)As/GaAs as well as (GaIn)As/Ga(PAs) multiple quantum well structures is studied by means of transient four-wave mixing (FWM) experiments. The wavepackets are generated by simultaneous excitation of several exciton transitions with laser pulses of about 100 fs duration. The time-integrated FWM signals exhibit a pronounced modulation superimposed on the overall decay which can be attributed to the quantum interference of the different eigenstates. In the time-resolved FWM signals this interference is not present, reflecting the interplay between many-body Coulomb effects and inhomogeneous broadening. This experimental technique is then employed to extract the exciton binding energies in pseudomorphic symmetrically strained (GaIn)As/GaIPAs) with various In contents.